Bodies of Law. - Hyde, Alan (Princeton University Press, 2001)
The most basic assertions about our bodies--that they are ours and distinguish us from each other, that they are private and have boundaries, races, and genders--are all political theories, constructed in legal texts for political purposes. So argues Alan Hyde in this first account of the body in legal thought. Hyde demonstrates that none of the constructions of the body in legal texts are universal truths that rest solely on body experience. Drawing on an array of fascinating case material, he shows that legal texts can construct all kinds of bodies, including those that are not owned at all.